Development of a Health Claim Verification Application using the Agile Method at Hospital X - Shafa Shafira Fatharani; Yuyun Yunengsih; Falaah Abdussalaam (CV. Science Tech Group, 2025)
Hospital X as one of the referral health facilities in the Cimahi area and its surroundings faces significant challenges in health claims management. This semi-digital process can result in significant financial losses and high operational costs. This research aims to build an application for the health claim verification process with the results of analysis at X Hospital. Developed a web-based health claims verification application with Agile methods that integrates ICD-10 standards and artificial intelligence (AI) to automate document checks, reduce human error, and speed up the verification process. The research uses agile methods with system development through Scrum. Key frameworks include Flask-Python (backend), Bootstrap 5 (frontend), and SQLite/PostgreSQL (database). Data is collected through interviews with medical staff and observation of existing verification processes. Implementation during 4 sprints resulted in a reduction in verification time from 3-5 days to <24 hours. The claim reduction is rejected from 8% to 2.5% through automatic validation. Multi-role system with 4 separate dashboards (admin, medical staff, verifier, participant). Pre-screening AI integration detects 92% of nominal anomalies of claims. This app is proven to improve verification accuracy and faster time efficiency. The success of the implementation of Agile is demonstrated by the ability to adapt to 12 changes in the requirements of the development time.